Borophene: a 2D wonder shaping the future of nanotechnology and materials science - Mishra, Raghvendra Kumar; Sarkar, Jayati; Verma, Kartikey; Chianella, Iva; Goel, Saurav; Nezhad, Hamed Yazdani (Elsevier, 2025)
Two-dimensional (2D) materials have attracted considerable research interest due to their precisely defined properties and versatile applications. In this realm, borophene - a single atomic sheet of boron atoms arranged in a honeycomb lattice - has emerged as a promising candidate. While borophenes were theoretically predicted to have unique structural, optical, and electronic properties, the experimental synthesis of crystalline borophene sheets was first demonstrated on metal substrates in 2015, marking a crucial milestone. Since then, research efforts have focused on controlling the synthesis of semiconducting borophene polymorphs and exploring their novel physical characteristics. This review aims to explore the potential of 2D materials, specifically borophene, in various technological fields such as batteries, supercapacitors, fuel cells, and more. The analysis emphasises meticulous scrutiny of synthesis techniques due to their fundamental importance in realising borophene's properties. Specifically, the high carrier mobilities, tuneable bandgaps, and exceptional thermal conductivity of borophene are highlighted. By providing a comprehensive outlook on the significance of borophene in advancing materials science and technologies, this review contributes to shaping the landscape of 2D material research.
Keywords: Borophene; 2D nanomaterials; Synthesis; Properties; Energy storage; Energy harvesting; Flexible electronics